The mitral regurgitation effects of cardiac structure and function in left ventricular noncompaction - Qing Zou (Nature Portfolio, 2021)
Abstract This study evaluated the effects of mitral regurgitation (MR) on cardiac structure and function in left ventricular noncompaction (LVNC) patients. The clinical and cardiovascular magnetic resonance (CMR) data for 182 patients with noncompaction or hypertrabeculation from three institutes were retrospectively included. We analyzed the difference in left ventricular geometry, cardiac function between LVNC patients with and without MR. The results showed that patients with MR had a worse New York Heart Association (NYHA) class and a higher incidence of arrhythmia (P < 0.05). MR occurred in 48.2% of LVNC patients. Compared to LVNC patients without MR, the two-dimensional sphericity index, maximum/minimum end-diastolic ratio and longitudinal shortening in LVNC patients with MR were lower (P < 0.05), and the peak longitudinal strain (PLS) of the global and segmental myocardium were obviously reduced (P < 0.05). No significant difference was found in strain in LVNC patients with different degree of MR; end diastolic volume, end systolic volume, and global PLS were statistically associated with MR and NYHA class (P < 0.05), but the non-compacted to compacted myocardium ratio had no significant correlation with them. In conclusion, the presence of MR is common in LVNC patients. LVNC patients with MR feature more severe morphological and functional changes. Hypertrabeculation is not an important factor affecting structure and function at the heart failure stage.